Modeling Study on Oil Particle Filtration Performance of a Composite Coalescing Filter - Lyu, Le; Zhang, Jun; Xu, ChengWei (Frontiers in Energy Research, 2022)
The traditional theory model is not suitable for the simulation of oil particles filtration process of the composite filter due to its huge difference of fiber diameter. In this paper, the concept of fiber dispersion σ was introduced into mathematical model for describing the dynamic filtration process of composite filter. The results show that the model is in good agreement with the experimental data. As the packing density is constant, the higher fiber dispersion, the better performance is. In addition, the effect of different factors on efficiency of different mechanisms were discussed. For fine particles (<0.1 μm), the diffusion is dominant mechanism. For coarse particles (>1 μm), the inertia impaction mechanism dominates the filtration efficiency. The fiber diameter has a significant effect on the inertia impaction mechanism. The single fiber efficiency by inertia impaction mechanism is obviously affected by filtration velocity. The packing density have effect on all mechanisms except for diffusion mechanism. Moreover, such a model would contribute to an accurate prediction of the dynamic filtration performance of composite filter with polydisperse fiber diameter and to improve performance by adjusting parameters reasonably.